Subjektive und objektive Zeit Aristoteles und die moderne Zeit-Theorie - Detel, Wolfgang (CHRONOI, 2021)
This essay examines the differentiation between subjective and objective time in Aristotle and in modern theories of time. It aims to show that (i) Aristotle does make this distinction but regards subjective and objective time as compatible, whereas (ii) modern theories of time have sharpened this distinction into a strict duality, but (iii) a sharp division of this kind is theoretically untenable.